Strain Characteristics of Large-Size Non-Studded Concrete-Filled Steel Tube Column under Construction - Zhenyu Zhang; Zhensheng Jia; Quan Jin; Haitao Zhang; Dongping Mei; Huifeng Zhang; Jin Mao; Lun Xiong (Buildings, 2024)
Interplay between the outer steel tubes and the core concrete provides an important guarantee for the superior performance of concrete-filled steel tube (CFST) columns compared to that of reinforced concrete columns. In order to optimize the construction of the large-size non-studded CFST columns in an on-going practical project, the strain distributions in the column under construction were measured and tracked, and the law of the strain distributions of the column under construction is revealed. The study finds that the plane section assumption was not applicable to the strain distributions of the column. Nonlinear variations in the strain levels were observed under bi-directional bending of the column. The absence of studs inside the steel tube significantly weakened the interplay of the outer steel tube and the core concrete by means of a significant slip between the concrete and the steel tube at the column corners. The concrete and the steel tube tended to be stressed and deformed independently. Practical suggestions are given for the design and construction of this type of column. The study results are expected to lay a basic and valuable foundation for in-depth investigations on the mechanical behavior of large-size non-studded concrete-filled steel tube columns under construction.